Achieving Autism Accreditation in Cat A Prison. (June 2022) - Daly, Rachel; Motherskill, Kimbia
Abstract : Aims: To ensure autististic prisoners are understood and receive necessary support in custodial environment. Methods: 1. Prison healthcare staff and discipline staff jointly trained about autism and how it is best managed in prison setting. 2. Promotion re-education aids for prisons visually and verbally. 3. Prison staff as autistic champions. 4. Accessible autistic spectrum lead in healthcare team to coordinate need. Results: priority that prison becomes autism accredited by national autistic society in progress. Conclusion: There is increase of prisoners with neurodevelopmental disorders and ensuring their needs met in prison and this is CAT A challenging prison environment.